Thermal degradation and morphology of Polymer blends comprising Poly(ε-caprolactone) and epoxidized natural rubber with addition of phenol as catalyst / Kamilah Binti Mohd. Alwai - Mohd. Alwai, Kamilah (Faculty of Applied Sciences, 2009)
Poly(ε-caprolactone) (PCL) is an aliphatic polyester. The PCL chains with weight-average molecular weight (Mw) of 4,200 g mol-1 are relatively short and contains terminal hydroxyl group. In blends with epoxidized natural rubber with 50% epoxidation level (ENR) (Mw = 700,000 g mol-1) as well as the addition of phenol as catalyst, thermal properties and morphology of PCL/ENR/phenol blends were investigated. The FTIR studies show that there are no chemical changes for the neat polymers and the blends when phenol is added. Morphologies of PCL/ENR/phenol blends show that the PCL spherulites become smaller than that of the neat spherulites when phenol is added to the system. The degradation temperature experiments of the blends show that the T5% wt loss of the blends is lower than that of ENR.